Isothermal aging kinetics in the Cu-19 at.%Al alloy - Adorno, A. T.; Guerreiro, M. R.; Benedetti, Assis Vicente [UNESP] (Elsevier B.V., 2001)
The influence of the disordered (Cu)-alpha phase in the isothermal aging kinetics of the Cu-19 at.%Al alloy was studied using microhardness measurements, optical and scanning electron microscopy and X-ray diffractometry. The results indicate that the beta'-->(alpha+gamma (1)) decomposition reaction rate increases with the increase of the temperature in the range between 150 and 500 degreesC and at 600 degreesC the reaction is delayed by the alpha phase precipitation. The value obtained for the activation energy indicates an interface diffusion controlled reaction. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: alloys; precipitation; mechanical properties; X-ray diffraction; scanning electron microscopy